Improving the canolol amount and the yield of expressed canola oil applying combined pretreatments - Cortese, C.M. (2018)
Canolol is a potent natural antioxidant. It exhibits antimutagenic and anticarcinogenic properties, showing an even more potent antimutagenic activity than that of α-tocopherol and flavonoids. This compound is formed due to high temperatures during processing of some seeds of brassica family, like canola. The nutritional value of canola oil can be increased by increasing the content of canolol, subjecting the seeds to different pretreatments (steam, microwaves). The aim of this work was to study treatments applied to canola seeds in order to improve the quality of the expressed oil, increasing the amount of canolol, and also to obtain higher yields of oil by pressing. Canola seeds were subjected to different treatments: -Hydrothermal (HT), by exposing the grains to steam in an autoclave; -Microwave (MW), irradiation in a microwave oven; Combination of both treatments (HT-MW): exposing the seeds to water vapor and then microwave irradiating until grains reached a 7% moisture, dry basis. Oil was extracted from pretreated and untreated samples by pressing using a helical screw press. Oil yield was determined by evaluating the residual oil remaining in the press cake. Canolol content was determined in all samples by HPLC. The combined pretreatment HT-MW significantly increased the amount of canolol in oil (495ppm in contrast with 5ppm in untreated samples) and significantly improved its oxidative stability. Moreover, this pretreatment generated the highest oil yield by expression, extracting 86% of the total oil. While, by pressing untreated canola, 68% of the total oil in grains was obtained, in hydrothermally pretreated samples it was extracted a 76% of the oil and 8% in the case of only irradiated with microwaves samples. Furthermore, SEM micrographs showed a more open structure in samples treated by combined pretreatment HT-MW, which could have improved the availability of oil, favoring the oil expression process.